A Remark on the Blow-up Criterion of Strong Solutions and Regularity for Weak Solutions of Navier-Stokes Equations (Journal of Partial Differential Equations, 2008)
IWe give blow-up criteria of strong solutions of Navier-Stokes equations with its initial data in Besov spaces and consider the regularity of Leray-Hopf solutions of the equation.
Keywords: Naiver-Stokes equations; blow-up; Littlewood-Paley decomposition; Leray-Hopf weak solution; Besov space